2020
DOI: 10.1186/s12889-020-8331-7
|View full text |Cite
|
Sign up to set email alerts
|

Human fertility in relation to education, economy, religion, contraception, and family planning programs

Abstract: Background: The world population is expected to increase greatly this century, aggravating current problems related to climate, health, food security, biodiversity, energy and other vital resources. Population growth depends strongly on total fertility rate (TFR), but the relative importance of factors that influence fertility needs more study. Methods: We analyze recent levels of fertility in relation to five factors: education (mean school years for females), economy (Gross Domestic Product, GDP, per capita)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 92 publications
12
81
0
3
Order By: Relevance
“…The study found that 64.95% of women desired more children, and this ranged from 34.9% in South Africa to 89.34% in Niger. This finding is comparable to previous studies [ 34 , 35 ]. However, it is higher than what was found in other studies [ 36 – 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The study found that 64.95% of women desired more children, and this ranged from 34.9% in South Africa to 89.34% in Niger. This finding is comparable to previous studies [ 34 , 35 ]. However, it is higher than what was found in other studies [ 36 – 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, women who are working are less likely to desire more children. These findings corroborate several previous studies which have revealed that higher socioeconomic status is associated with lower fertility desires [ 34 , 40 – 44 ]. This result can be discussed within the context of the wealth flow hypotheses postulated by Caldwell [ 45 , 46 ], who elucidates that, in contemporary societies, women and families who are in the high socioeconomic strata tend to view more children as additional burden that has the tendency to strain their resources, including time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Why would human fertility decline when individuals are on average more comfortable and healthier than ever? The correlates and proximate causes are broadly understood: total fertility rate (TFR) declines across societies with increasing education and economic development (177).…”
Section: Discussion: Causation In Human Sociobiological Evolutionmentioning
confidence: 99%
“…It has been controlled in the developed world mostly whereas consistently found high in the developing countries even in the beginning of the 21st century. Education along with more awareness, access to family planning services, and adoption of family planning methods are the major causes of population control in the world (Götmark & Andersson, 2020;Mandl, 2019;Steer & Wathne, 2010;Tropf & Mandemakers, 2017; Ullah, Ashraf, Tariq, Aziz, .…”
Section: Introductionmentioning
confidence: 99%